Given:
-2y + 5z = -3 (first equation)
y = -5x - 4z - 5 (second equation)
x = 4z + 4 (third equation)
Solution:
PART 1
Substitute x with (4z + 4) in the second equation
y = -5x - 4z - 5
y = -5(4z + 4) - 4z - 5
Then simplify
y = -20z - 20 - 4z - 5
add like terms
y = -20z - 4z - 20 - 5
y = -24z - 25
PART 2 : Find the value of z
We got y is equal to (-24z - 25). Substitute y with (-24z - 25) in the first equation, and we'll find the value of z.
-2y + 5z = -3
-2(-24z - 25) + 5z = -3
48z + 50 + 5z = -3
add like terms
48z + 5z = -3 - 50
53z = -53
z = -53/53
z = -1
The value of z is equal to -1
PART 3: Find y and x
Find the value of y by substitution of -1 in the place of z.
y = -24z - 25
y = -24(-1) - 25
y = 24 - 25
y = -1
The value of y is equal to -1
Find the value of x by substitution of -1 in the place of z.
x = 4z + 4
x = 4(-1) + 4
x = -4 + 4
x = 0
The value of x is equal to 0